2013
DOI: 10.1038/srep01934
|View full text |Cite
|
Sign up to set email alerts
|

Chiral plasmonics of self-assembled nanorod dimers

Abstract: Chiral nanoscale photonic systems typically follow either tetrahedral or helical geometries that require four or more different constituent nanoparticles. Smaller number of particles and different chiral geometries taking advantage of the self-organization capabilities of nanomaterials will advance understanding of chiral plasmonic effects, facilitate development of their theory, and stimulate practical applications of chiroplasmonics. Here we show that gold nanorods self-assemble into side-by-side orientated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
234
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(242 citation statements)
references
References 33 publications
7
234
1
Order By: Relevance
“…However, these asymmetrically coupled plasmonic structures are often not thermodynamically favourable, and the self-assembly of such structures remains a challenge. By judicious selection of linker molecules, the bonding direction of gold nanorods can be controlled to form directional nanodimers and, as has been demonstrated recently, chiral plasmonic structures 18 . Nevertheless, all previously reported nanorod assemblies, in general, tend to aggregate and align side by side or end to end as a consequence of maximized interparticle interaction and minimized surface energy, and there is no controlled structural selection with a longitudinal symmetry-breaking phenomenon [19][20][21] .…”
mentioning
confidence: 94%
“…However, these asymmetrically coupled plasmonic structures are often not thermodynamically favourable, and the self-assembly of such structures remains a challenge. By judicious selection of linker molecules, the bonding direction of gold nanorods can be controlled to form directional nanodimers and, as has been demonstrated recently, chiral plasmonic structures 18 . Nevertheless, all previously reported nanorod assemblies, in general, tend to aggregate and align side by side or end to end as a consequence of maximized interparticle interaction and minimized surface energy, and there is no controlled structural selection with a longitudinal symmetry-breaking phenomenon [19][20][21] .…”
mentioning
confidence: 94%
“…For example, a single bio-entity that binds to the DNA arms and its subsequent reactions with other chemical compounds could trigger a series of conformational changes of the plasmonic metamolecule. With a combination of single-particle dark-field microscopy and CD spectroscopy 22 , the conformation changes of the plasmonic molecule arising from single bio-entity binding could be optically detected in real time. In addition, the unprecedented level of spatial and temporal control offered by DNA nanotechnology may advance the development of smart nanomaterials for plasmonics.…”
Section: Left-handedmentioning
confidence: 99%
“…Owing to close proximity, the excited plasmons in the two AuNRs can be strongly coupled 18 . The two crossed AuNRs constitute a 3D plasmonic chiral object [19][20][21][22] , which generates a theme of handedness when interacting with left-and right-handed circularly polarized light, giving rise to strong CD. …”
mentioning
confidence: 99%
“…Stronger effects could be obtained in systems of achiral nanoparticles arranged in a chiral superstructure with strong interparticle interaction [13][14][15][16] . Recently, Kotov and colleagues 17 demonstrated that the chiroptical activity of a chiral particle dimer is intense enough to monitor on a single nanoparticle level. The most intuitive approach to obtain large chiroptical activity is by forming nanoparticles with an actual chiral shape such as a gammadion or a helix.…”
mentioning
confidence: 99%